Pyoderma Gangrenosum, Acne, and Hidradenitis Suppurativa Syndrome: A Case Report and Literature Review - Jundong Huang; Lemuel Shui-Lun Tsang; Wei Shi; Ji Li (Frontiers in Medicine, 2022)
Pyoderma gangrenosum, acne, and hidradenitis suppurativa syndrome is a rare inflammatory disease characterized by pyoderma gangrenosum (PG), mild to severe facial acne, and hidradenitis suppurativa (HS). It only affects the skin and represents cutaneous characteristics of a spectrum of autoinflammation. Lack of pyogenic sterile arthritis (PA) distinguishes the pyoderma gangrenosum, acne, and hidradenitis suppurativa (PASH) syndrome from pyogenic arthritis, pyoderma gangrenosum, acne, and hidradenitis suppurativa (PA-PASH), pyoderma gangrenosum, acne, hidradenitis suppurtiva, and ankylosing spondylitis (PASS), and pyogenic arthritis, pyoderma gangrenosum, and acne (PAPA) syndromes. The exact etiology and pathogenesis of PASH syndrome remain unknown. Both PG and HS are contained in the spectrum of neutrophilic dermatitis, which is considered as an autoinflammatory syndrome. From a pathophysiological point of view, they show similar mechanisms, including neutrophil-rich cutaneous infiltration and overexpression of the interleukin-1 (IL-1) family. These findings provide guidance for these intractable diseases. In this review, we described a case of PASH syndrome in a patient who initially failed to respond to immunosuppressive treatment but responded to a combination of colchicine and thalidomide. We reviewed the relevant literature that focuses on PASH syndrome management.